Thick and Thin : Moral Argument at Home and Abroad - Walzer, Michael (Book collections on Project MUSE., 1994)
"When Michael Walzer's Spheres of Justice was published ten years ago, the front page of The New York Times Book Review hailed the work as "an imaginative alternative to the current debate over distributive justice." Now in Thick and Thin, Walzer revises and extends his arguments in Spheres of Justice, framing his ideas about justice, social criticism, and national identity in light of the new political world that has arisen in the past decade. Walzer focuses on two different but interrelated kinds of moral argument: maximalist and minimalist, thick and thin, local and universal." "According to Walzer the first, thick type of moral argument is culturally connected, referentially entangled, detailed, and specific; the second, or thin type, is abstract, ad hoc, detached, and general. Thick arguments play the larger role in determining our views about domestic justice and in shaping our criticism of local arrangements. Thin arguments shape our views about justice in foreign places and in international society. The book begins with an account of minimalist argument, then examines two uses of maximalist arguments, focusing on distributive justice and social criticism. Walzer then discusses minimalism with a qualified defense of self-determination in international society, and concludes with a discussion of the (divided) self capable of this differentiated moral engagement." "Walzer's highly literate and fascinating blend of philosophy and historical analysis will appeal not only to those interested in the polemics surrounding Spheres of justice but also to intelligent readers who are more concerned with getting the arguments right."--Jacket.